2011
DOI: 10.1152/ajpcell.00093.2011
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic and glutamatergic agonists induce gamma frequency activity in dorsal subcoeruleus nucleus neurons

Abstract: The dorsal subcoeruleus nucleus (SubCD) is involved in generating two signs of rapid eye movement (REM) sleep: muscle atonia and ponto-geniculo-occipital (PGO) waves. We tested the hypothesis that single cell and/or population responses of SubCD neurons are capable of generating gamma frequency activity in response to intracellular stimulation or receptor agonist activation. Whole cell patch clamp recordings (immersion chamber) and population responses (interface chamber) were conducted on 9- to 20-day-old rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…The SubCD receives cholinergic input from the PPN, and projects to many areas, including the lateral geniculate nucleus and hippocampus (Datta et al 1998, 1999). We found that SubCD neurons were also capped to fire at gamma band frequencies, but the mechanism responsible for firing at these frequencies was identified as sodium-dependent subthreshold oscillations (Simon et al 2011; Urbano et al 2013), like those mediating gamma oscillations in some cortical interneurons (Llinas et al 1991). Therefore, we speculate that the generation of gamma band activity during REM sleep may primarily include the PPN-SubCD pathway, while during waking it may primarily use the PPN-Pf/intralaminar thalamus pathway.…”
Section: Gamma Band Activitymentioning
confidence: 91%
See 1 more Smart Citation
“…The SubCD receives cholinergic input from the PPN, and projects to many areas, including the lateral geniculate nucleus and hippocampus (Datta et al 1998, 1999). We found that SubCD neurons were also capped to fire at gamma band frequencies, but the mechanism responsible for firing at these frequencies was identified as sodium-dependent subthreshold oscillations (Simon et al 2011; Urbano et al 2013), like those mediating gamma oscillations in some cortical interneurons (Llinas et al 1991). Therefore, we speculate that the generation of gamma band activity during REM sleep may primarily include the PPN-SubCD pathway, while during waking it may primarily use the PPN-Pf/intralaminar thalamus pathway.…”
Section: Gamma Band Activitymentioning
confidence: 91%
“…We found that almost all cells in the mesopontine pedunculopontine nucleus (PPN) and its ascending target, the intralaminar thalamic parafascicular nucleus (Pf), as well as the descending target, the SubCoeruleus nucleus dorsalis (SubCD), were capped to fire at gamma frequencies (40–60 Hz), but no higher (Simon et al 2010, 2011; Kezunovic et al 2012). We found that this activity was subserved by voltage-dependent, high threshold N- and P/Q-type calcium channels in the PPN and Pf (Kezunovic et al 2011, 2012), and by sodium-dependent subthreshold oscillations in the SubCD (Simon et al 2011). We localized N- and P/Q-type calcium channel-mediated gamma oscillations to the dendrites of PPN and Pf cells (Hyde et al 2013a, 2013b).…”
Section: Gamma Band Activitymentioning
confidence: 99%
“…We reasoned that blockade of a signaling pathway involved in evolutionarily derived sleep loss would have little effect on sleep in surface populations while increasing sleep in cavefish. We tested antagonists directed toward glutamatergic, seretonergic, histaminergic, cholinergic, dopaminergic, and noradrenergic systems that have previously been implicated in sleep [Cirelli, 2009;Hunsley et al, 2006;Parmentier et al, 2002;Pollock and Mistlberger, 2003;Simon et al, 2011;Stone et al, 1992;Wisor et al, 2003] ( fig. 1 a).…”
Section: Resultsmentioning
confidence: 99%
“…The amino acid neurotransmitters GABA and glutamate have also been implicated in the regulation of sleep. Injection of glutamate, or inhibition of GABA signaling in the dorsal subcoeruleus, a brain region involved in REM sleep, potently induces REM sleep [Pollock and Mistlberger, 2003;Simon et al, 2011]. Furthermore, pharmacological blockade of the glutamate N -methyl-daspartic acid (NMDA) receptor disrupts sleep [Stone et al, 1992].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the two calcium channel subtypes in the PPN are modulated by different intracellular pathways, N-type by the cAMP/ PK pathway, and P/Q-type via the CaMKII pathway. Additionally, there are three cell types in the PPN, those bearing only N-type calcium channels, those with both N-and P/Q-type, and those with only P/Qtype calcium channels [28,29]. The implications from these results are that, i) there is a ''waking'' pathway mediated by CaMKII and P/Qtype channels and a ''REM sleep'' pathway mediated by cAMP/PK and N-type channels; and ii) different PPN cells fire during waking (those with N+P/Q and only P/Q-type) vs REM sleep (those with N+P/Q and only N-type) [28,29].…”
Section: Discovery Of Electrical Coupling and Of Gamma Band Activitymentioning
confidence: 99%